2018
DOI: 10.2147/ijn.s163721
|View full text |Cite
|
Sign up to set email alerts
|

Iron–gold alloy nanoparticles serve as a cornerstone in hyperthermia-mediated controlled drug release for cancer therapy

Abstract: IntroductionThe efficacy of a chemotherapy drug in cancer therapy is highly determined by the ability to control the rate and extent of its release in vivo. However, the lack of techniques to accurately control drug release drastically limits the potency of a chemotherapy drug.Materials and methodsHere, we present a novel strategy to precisely monitor drug release under magnetic stimulation. Methotrexate (MTX), an anticancer drug, was covalently functionalized onto iron–gold alloy magnetic nanoparticles (Fe–Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The presence of Fe and Au in FeAu Nps was further confirmed through XRD, which showed distinct 2 θ peaks at 38.6, 44.8, and 64.4° that correspond to the (111), (200), and (220) planes of face center cubic (FCC) of gold and the 2 θ peaks at 43.9 and 64.8 that correspond to the (110) and (200) planes of body-centered cubic (BCC) in iron, thereby further confirming the presence of Fe and Au in FeAu Nps ( Figure 1 d). These results were firmly consistent with our previous study as well as with those of Krishnamurthy et al [ 21 , 28 ], thereby confirming the formation of FeAu Nps.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The presence of Fe and Au in FeAu Nps was further confirmed through XRD, which showed distinct 2 θ peaks at 38.6, 44.8, and 64.4° that correspond to the (111), (200), and (220) planes of face center cubic (FCC) of gold and the 2 θ peaks at 43.9 and 64.8 that correspond to the (110) and (200) planes of body-centered cubic (BCC) in iron, thereby further confirming the presence of Fe and Au in FeAu Nps ( Figure 1 d). These results were firmly consistent with our previous study as well as with those of Krishnamurthy et al [ 21 , 28 ], thereby confirming the formation of FeAu Nps.…”
Section: Resultssupporting
confidence: 94%
“…However, as the nanoparticles are not coated with any biocompatible material, the cytotoxic effects of nanoparticles alone cannot be avoided. We have previously demonstrated that chemodrug release to target cancer cells is achievable using hyperthermia [ 21 ]. Further, we used the iron–gold core–shell nanoparticles toward Magnetic Resonance Imaging (MRI) and Optical coherence tomography (OCT) imaging using photostimulation, showing a multitude of nanoparticle properties that can be exploited in biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…This study reflects the successful report of iron–gold nanohybrids as a single system for multifunctional uses in cancer therapy [ 105 ]. In another example, Yun Quan-Li et al have covalently attached a cytotoxic agent such as methotrexate to iron–gold alloy NPs and reported that with the increase in the applied magnetic field, the release of methotrexate increased in an incremental manner [ 111 ].…”
Section: Iron–gold Bifunctional Nanoparticlesmentioning
confidence: 99%
“…Magnetic nanoparticles can be heated under the magnetic field leading to direct killing of cancer cells, or by releasing the carried drug to kill the cancer cells [ 265 , 266 ]. Many kinds of magnetic nanoparticles (superparamagnetic iron-oxide, Fe 3 O 4 or Fe 2 O 3 , Mn–Zn, and Fe–Au nanoparticles) are created and surface-modified using aminosilane, antibodies, PEG-phospholipids, or cyclic tripeptide of arginine-glycine-aspartic acid for the treatment of glioblastoma multiforme tumors [ 267 , 268 , 269 , 270 , 271 ]; or in the activation of reactive oxygen species via the p53 pathway in killing HepG2 human hepatocellular carcinoma and A549 human lung adenocarcinoma cells [ 272 ].…”
Section: Application Of Alloy Nanoparticles In the Biological Fielmentioning
confidence: 99%